2010
DOI: 10.1126/science.1177118
|View full text |Cite
|
Sign up to set email alerts
|

How the Shape of an H-Bonded Network Controls Proton-Coupled Water Activation in HONO Formation

Abstract: Many chemical reactions in atmospheric aerosols and bulk aqueous environments are influenced by the surrounding solvation shell, but the precise molecular interactions underlying such effects have rarely been elucidated. We exploited recent advances in isomer-specific cluster vibrational spectroscopy to explore the fundamental relation between the hydrogen (H)-bonding arrangement of a set of ion-solvating water molecules and the chemical activity of this ensemble. We find that the extent to which the nitrosoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
119
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(125 citation statements)
references
References 23 publications
6
119
0
Order By: Relevance
“…Furthermore, the distribution of low-lying isomers at 220 K, including both highly populated critical and less-populated local-minimum isomers, is obtained. In agreement with the results of Relph et al (16), there is no observed charge transfer between the NO + and the water clusters in the n = 1 or n = 2 NO + (H 2 O) n clusters, indicating that these small clusters are inert. The charge transfer observed for clusters with n ≥ 3 suggests the possible formation of HONO from the NO + (H 2 O) n clusters.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the distribution of low-lying isomers at 220 K, including both highly populated critical and less-populated local-minimum isomers, is obtained. In agreement with the results of Relph et al (16), there is no observed charge transfer between the NO + and the water clusters in the n = 1 or n = 2 NO + (H 2 O) n clusters, indicating that these small clusters are inert. The charge transfer observed for clusters with n ≥ 3 suggests the possible formation of HONO from the NO + (H 2 O) n clusters.…”
supporting
confidence: 81%
“…Using quantum molecular dynamics, Ye and Cheng (15) suggested possible structures and corresponding IR spectra for NO + (H 2 O) n (n = 1-3) clusters. In a major experimental breakthrough, Relph et al (16) showed that the extent to which reaction 1 produces HONO and H + (H 2 O) n depends on the size and shape of the water clusters. Another key finding was that the reactions for HONO production start with the n = 4 water cluster.…”
mentioning
confidence: 99%
“…However, one can reduce spectral congestion by cooling ions to low temperatures [26], which has the effect of narrowing the measured absorption bands. One can also separate spectral contributions from multiple conformers by performing multi-laser experiments [27][28][29], as long as each conformer has at least one unique spectroscopic transition. After having implemented both of these techniques in our laboratory, we find that it is possible to study systems with up to about 10-15 amino acid residues before spectral congestion again becomes a limiting factor.…”
mentioning
confidence: 99%
“…Notwithstanding the importance of water-mediated ground-and excited-state PT, these processes are not well understood, and only a few studies have emerged to shed light on the underlying mechanistic details and dynamics. For example, a recent study of small NO + (H 2 O) n clusters investigated how the shape of h-bonded network controls proton-coupled water activation in HONO formation in the ionosphere [16]. Sequential PT through water bridges in acid-base reactions has been studied by time-resolved experiments in which the reaction has been initiated by an optical trigger exciting the photoacid [17].…”
mentioning
confidence: 99%
“…Water is no longer seen as just a solvent, but is an active participant in a variety of processes such as enzyme catalysis and membrane transport. Water has also been shown to catalyze reactions [29] which are important in biology and atmospheric chemistry [16,30]. Proton-coupled electron transfer in DNA is mediated by water chains [11].…”
mentioning
confidence: 99%